Catalytic hydrotreatment of the high-boiling-point fraction of soybean straw biocrude in a mixed hydrogen donor. (15th February 2022) - Wang, Zhi-Cong; Chen, Dabo; Shan, Ya-Qi; Lin, Lin-Xin; Duan, Pei-Gao
Graphical abstract: Highlights: HBF of the soybean straw biocrude was effectively hydrotreated in an HDS mixture. H2 and Pt, particular the HDS played a critical role during the hydrotreatment process. The S was the easiest heteroatom to be removed, followed by N and O. 98.6% S, 96.2% N, and 87.1% O were removed from the initial feedstock. The resulting product oil had better properties than the 0# diesel. Abstract: In this study, a high-boiling point fraction (HBF, 141-220 °C) from vacuum distillation of a biocrude produced from hydrothermal liquefaction of soybean straw was hydrotreated in a hydrogen donor solvent (HDS) mixture consisting of tetralin and decalin at a mass ratio of 1:1. Effects of temperature (300–450 °C), time (1–6 h), H2 pressure (0.01–10 MPa), and Pt/C loading (0–40 wt%) on the products distribution and properties of the treated oil were examined. Increasing the temperature, time, and catalyst loading or decreasing the H2 pressure would reduce the treated oil yield and increase the gas and solid product yields. The presence of HDS mixture played a critical role in favoring the production of treated oil, reducing the formation of gas and solid products, and the removal of N, O, and S from the HBF. Under optimal reaction conditions, 96.3% of N, 87.1% of O, and 98.5% of S were removed from the initial feedstock. The treated oil mainly consisted of saturated hydrocarbon(∼40%, C8-C20) and aromatics(∼41%, naphthalene and benzene derivatives), which was had a comparable cetane number and better combustion characteristics relative to the market 0# diesel.